Real-world effectiveness of sofosbuvir plus ribavirin for chronic hepatitis C genotype 2 in Asia: a systematic review and meta-analysis. Issue 1 (29th June 2018) - Wei, Bin; Ji, Fanpu; Yeo, Yee Hui; Ogawa, Eiichi; Zou, Biyao; Stave, Christopher D; Dang, Shuangsuo; Li, Zongfang; Furusyo, Norihiro; Cheung, Ramsey C; Nguyen, Mindie H
Abstract : Background: Sofosbuvir plus ribavirin (SOF+RBV) for 12 weeks is the standard treatment for chronic hepatitis C (CHC) genotype 2 (GT2) in most of Asia despite availability of new CHC medications. SOF-RBV real-world effectiveness has only been reported in small and/or single-centre studies. Our goal was to determine the real-world effectiveness of 12-week SOF+RBV therapy for CHC GT2 in Asia. Methods: A systematic search on PubMed and Embase was conducted through 30 June 2017. We identified full articles and conference proceedings of at least 10 adult patients with CHC GT2 treated with SOF+RBV for 12 weeks under real-world setting in Asia. Results: A total of 2208 patients from 13 studies were included. The pooled sustained virological response 12 weeks after the end of treatment (SVR12) was 95.8% (95% CI 94.6% to 96.9%) with non-significant heterogeneity (I 2 =34.4%). Anaemia (27.9%) was the most common adverse event (AE), with serious AEs in 2.0% and only 0.7% discontinued therapy prematurely. In subgroup analyses, patients with cirrhosis had 8.7% lower SVR12 than non-cirrhotic patients ( P <0.0001), and treatment-experienced patients had 7.2% lower SVR12 than treatment-naïve patients ( P =0.0002). Cirrhotic treatment-experienced patients had the lowest SVR12 at 84.5%. There were no significant differences in pooled SVR12 among patient subgroups: RBV dose reduction versus no dose reduction ( P =0.30); hepatocellular carcinoma (HCC) versus no HCC ( P =0.10); GT 2a versus 2b ( P =0.86); and <65 vs ≥65 years of age ( P =0.20). Conclusions: SOF+RBV for 12 weeks was safe and effective for patients with CHC GT2 in Asia, although those with cirrhosis and prior treatment failure had a lower pooled SVR12 rate. Trial registration number: CRD42017067928.